The Half-Life of Policy Rationales : How New Technology Affects Old Policy Issues - Klein, Daniel B.; Foldvary, Fred E., 1946- (Book collections on Project MUSE., 2003)
The Half-Life of Policy Rationales argues that the appropriateness of policy depends on the state of technology, and that the justifications for many public policies are dissolving as technology advances. As new detection and metering technologies are being developed for highways, parking, and auto emissions, and information becomes more accessible and user-friendly, this volume argues that quality and safety are better handled by the private sector. As for public utilities, new means of producing and delivering electricity, water, postal, and telephone services dissolve the old natural-monopo.